Ketogenic Diets and Chronic Disease: Weighing the Benefits Against the Risks - Crosby, Lee; Davis, Brenda; Joshi, Shivam; Jardine, Meghan; Paul, Jennifer; Neola, Maggie; Barnard, Neal D. (Frontiers in Nutrition, 2021)
Very-low-carbohydrate ketogenic diets have been long been used to reduce seizure frequency and more recently have been promoted for a variety of health conditions, including obesity, diabetes, and liver disease. Ketogenic diets may provide short-term improvement and aid in symptom management for some chronic diseases. Such diets affect diet quality, typically increasing intake of foods linked to chronic disease risk and decreasing intake of foods found to be protective in epidemiological studies. This review examines the effects of ketogenic diets on common chronic diseases, as well as their impact on diet quality and possible risks associated with their use. Given often-temporary improvements, unfavorable effects on dietary intake, and inadequate data demonstrating long-term safety, for most individuals, the risks of ketogenic diets may outweigh the benefits.